(untitled) (MAUSAM, 1985)
Crop potential under rainfed conditions based on Moisture Availability Index (MAI) and Stored Soil Moisture, (SSM) was assessed for selected stations in Andhra Pradesh. Using MAI, crops of different durations and optimum dates of sowing are indicated. Nizamabad district has the highest crop potential and Anantapur district has the lowest crop potential. In general, coastal districts and northern districts of Telangana have higher crop potential than the remaining districts of Andhra Pladesh.